On new interpretations of the aim of spatial equivalency - Hahne, Ulf (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
Growing disparities and shrinking regions caused a discussion on regional equivalency in Germany. The essay discusses consequences of abolishing this constitutional aim versus adjusting the instruments with special regards to minimal standards of social infrastructure. The author pleads — in respect of the new European aim of territorial cohesion — for maintaining the aim and a sensible quest for flexible instruments without neglecting the potentials and talents of the periphery.